2021
DOI: 10.3390/polym13101598
|View full text |Cite
|
Sign up to set email alerts
|

Toxic or Not Toxic, That Is the Carbon Quantum Dot’s Question: A Comprehensive Evaluation with Zebrafish Embryo, Eleutheroembryo, and Adult Models

Abstract: Carbon quantum dots (CQDs) are emerging novel nanomaterials with a wide range of applications and high biocompatibility. However, there is a lack of in-depth research on whether CQDs can cause acute or long-term adverse reactions in aquatic organisms. In this study, two different types of CQDs prepared by ammonia citrate and spermidine, namely CQDAC and CQDSpd, were used to evaluate their biocompatibilities. In the fish embryo acute toxicity test (FET), the LD50 of CQDAC and CQDSpd was about 500 and 100 ppm. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
(72 reference statements)
0
32
0
Order By: Relevance
“…Cytotoxicity of CdSe, CdTe, and InP was based on four QD formulations, including CdSe/CdS/ZnS QDs that have been modified with mercaptopropionic acid (CdSe-MPA) and CdSe/CdS/ZnS QDs encapsulated in PEGylated phospholipid (CdSe-Phos), and they were investigated. Surprisingly, two cancer cells—neuroblastoma (SH-SY5Y) and stomach adenocarcinoma (BGC-823)—exhibited various cytotoxic responses [ 120 ]. This study thereby brings vital insights to the reality that a combination of factors from the particle compositions and the level of cellular absorption determine the toxicity of QDs rather than being simply dependent on one factor.…”
Section: Challenges and Opportunities Of Cds: Safety Issuesmentioning
confidence: 99%
“…Cytotoxicity of CdSe, CdTe, and InP was based on four QD formulations, including CdSe/CdS/ZnS QDs that have been modified with mercaptopropionic acid (CdSe-MPA) and CdSe/CdS/ZnS QDs encapsulated in PEGylated phospholipid (CdSe-Phos), and they were investigated. Surprisingly, two cancer cells—neuroblastoma (SH-SY5Y) and stomach adenocarcinoma (BGC-823)—exhibited various cytotoxic responses [ 120 ]. This study thereby brings vital insights to the reality that a combination of factors from the particle compositions and the level of cellular absorption determine the toxicity of QDs rather than being simply dependent on one factor.…”
Section: Challenges and Opportunities Of Cds: Safety Issuesmentioning
confidence: 99%
“…However, more detailed studies of the biosafety and therapeutic mechanisms of CQDs are needed before the large-scale application of these materials. Including this study, many toxicity studies, using model organisms, have shown no adverse effects of these carbon-based nanomaterials on animals after short- and long-term ingestion [ 67 , 68 ]. Many processed foods consumed daily also contain CQDs [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDs were rapidly excreted from the body in the urine. Completely new results from the work of Chung et al [61] showed that carbon dots prepared from ammonium citrate and spermidine have low toxicity and bioaccumulation for zebrafish.…”
Section: Biocompatibility Of Carbon Dotsmentioning
confidence: 99%